2021
DOI: 10.1002/ejic.202100524
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Cobalt(III) Corrole with an S‐Bound DMSO Ligand

Abstract: We have synthesized a low-spin Co(III) complex of 5,15-bis(4nitrophenyl)-10-(2-methylcarboxyphenyl)corrole with an Sbound dimethylsulfoxide (DMSO) ligand (1DMSO) and determined the coordination mode through X-ray diffraction for the first time. UV-vis-NIR spectral data show that the DMSO ligand does not dissociate in MeCN solution, and EPR results indicate that the first oxidation is ligand centered and suggest that not only DMSO remains bound but a second apical ligand, possibly MeCN, binds to the cobalt cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…On the other hand, the first reduction of 5 in its bis-CN – form is located at E 1/2 = −1.10 V and is assigned to occur strictly on the NO 2 Ph substituents of the molecule given the threefold increase in current height for this process as compared to that for the first oxidation, an observation again consistent with three overlapping one-electron transfers to the non-interacting meso -NO 2 Ph substituents. It is worth noting that the potential for this process is similar to other previously reported p -nitrophenyl corroles, which display overlapping NO 2 Ph reductions at −1.10 to −1.13 V vs SCE. ,,,,,,, Moreover, the voltammogram for the bis-CN – adduct of 5 displays no evidence for a corrole-centered reduction when scanning up to −1.6 V. The fact that reduction of the NO 2 Ph substituents in the bis-CN – complex of 5 occurs before electron addition to the π-system or cobalt metal ion indicates that the LUMO of the NO 2 Ph group lies between the a 1u (π) and a 2u (π) (HOMO) and e.g. (π*) (LUMO) orbitals of the corrole, thus resulting in orbital interactions and charge transfer transitions between the two moieties and an observed hyperporphyrin spectrum.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…On the other hand, the first reduction of 5 in its bis-CN – form is located at E 1/2 = −1.10 V and is assigned to occur strictly on the NO 2 Ph substituents of the molecule given the threefold increase in current height for this process as compared to that for the first oxidation, an observation again consistent with three overlapping one-electron transfers to the non-interacting meso -NO 2 Ph substituents. It is worth noting that the potential for this process is similar to other previously reported p -nitrophenyl corroles, which display overlapping NO 2 Ph reductions at −1.10 to −1.13 V vs SCE. ,,,,,,, Moreover, the voltammogram for the bis-CN – adduct of 5 displays no evidence for a corrole-centered reduction when scanning up to −1.6 V. The fact that reduction of the NO 2 Ph substituents in the bis-CN – complex of 5 occurs before electron addition to the π-system or cobalt metal ion indicates that the LUMO of the NO 2 Ph group lies between the a 1u (π) and a 2u (π) (HOMO) and e.g. (π*) (LUMO) orbitals of the corrole, thus resulting in orbital interactions and charge transfer transitions between the two moieties and an observed hyperporphyrin spectrum.…”
Section: Resultssupporting
confidence: 80%
“…It is worth noting that the potential for this process is similar to other previously reported p-nitrophenyl corroles, which display overlapping NO 2 Ph reductions at −1.10 to −1.13 V vs SCE. 34,35,38,40,44,51,59,60 Moreover, the voltammogram for the bis-CN − adduct of 5 displays no evidence for a corrole-centered reduction when scanning up to −1.6 V. The fact that reduction of the NO 2 Ph substituents in the bis-CN − complex of 5 occurs before electron addition to the π-system or cobalt metal ion indicates that the LUMO of the NO 2 Ph group lies between the a 1u (π) and a 2u (π) (HOMO) and e.g. (π*) (LUMO) orbitals of the corrole, thus resulting in orbital interactions and charge transfer transitions between the two moieties and an observed hyperporphyrin spectrum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own laboratories have focused on elaborating an electrochemical litmus test for evaluating the innocence or noninnocence of transition-metal corroles ,,,,, and found that the presence of a facile reduction at potentials more positive than −0.20 V vs SCE (saturated calomel electrode) accompanied by a relatively small HOMO-LUMO gap (<1.0 V) could be used as an electrochemical diagnostic criterion to establish ligand noninnocence in these systems. Modulation of the orbital interactions, and thus the noninnocence of the corrole system, has been clearly demonstrated by changing the number and/or type of axial ligands bound to the central metal ion (mainly in the case of Mn, Fe, , and Co , derivatives), while the introduction of specific peripheral substituents has been suggested, in only a few cases, to facilitate conversion between the noninnocent [Cor •2– M II ] and innocent [Cor 3– M III ] configuration of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For the complexes previously studied by us, the ligand centered oxidation could be easily reproduced computationally for hexacoordinated Co(III) corroles, which show spin density mostly located in the ligand, and very little to none on the metal atom (Figure 3 in solution. [20] However, for strictly pentacoordinated cobalt corroles, our calculations still consistently predicted a metal centered process. A Co(III)/Co(IV) oxidation should be more favoured by two apical ligands instead of one, so how could the loss of a ligand cause the place of oxidation to shift from the corrole to the metal?…”
Section: Resultsmentioning
confidence: 60%